Protective role of soluble receptor for advanced glycation end-products in patients with non-alcoholic fatty liver disease. Issue 5 (May 2017) - Zelber-Sagi, Shira; Salomone, Federico; Kolodkin-Gal, Ilana; Erez, Noam; Buch, Assaf; Yeshua, Hanny; Webb, Muriel; Halpern, Zamir; Shibolet, Oren
Abstract: Background: Soluble receptor for advanced glycation end-products (sRAGE) exerts protective metabolic effects. Aims: To identify if sRAGE plays a protective role in NAFLD. Methods: sRAGE (n = 55) and Nε-(Carboxymethyl) lysine (CML) (n = 36) serum levels were measured in NAFLD patients. Liver steatosis and fibrosis were non-invasively quantified by the hepatorenal index and the NAFLD fibrosis score (NFS). Results: sRAGE levels were lower in NAFLD patients compared to controls (1207 ± 439 vs. 1596 ± 562 ng/l, P < 0.001) and were lower among subjects with moderate-severe steatosis compared with mild (1043 ± 287 vs. 1378 ± 506, P = 0.005). Higher sRAGE was associated with lower steatosis with adjustment for age, gender, BMI and fasting insulin (OR = 0.998, 0.996–0.999 95%CI, P = 0.018). CML was not correlated with liver steatosis (r = 0.07, P = 0.683), but was positively correlated with AST (r = 0.34, P = 0.04), GGT (r = 0.38, P = 0.023) and HbA1C (r = 0.37, P = 0.027). sRAGE tended to be higher in subjects with NFS < −1.455 compared with NFS > −1.455 (1287 ± 450 n = 36 vs. 1051 ± 364 n = 13, P = 0.08). While sRAGE was positively correlated with vegetables consumption (r = 0.268, P = 0.05), CML levels were not associated with sRAGE or dietary intake. sRAGE increased following a 3 month-lifestyle intervention (1194 ± 446 vs. 1367 ± 440 n = 31, P < 0.001) and change in sRAGE levels was negatively correlated with change in ALT levels (r = −0.37, P = 0.041). Conclusion: sRAGE plays a protective role in NAFLD and it is influenced by lifestyle.